Deadlock characterization and control of flexible assembly systems with Petri nets. (January 2018) - Xing, Keyi; Wang, Feng; Zhou, Meng Chu; Lei, Hang; Luo, Jianchao
Abstract: Efficient deadlock controllers are critical in the operation of automated manufacturing systems. This work focuses on a deadlock control problem for flexible assembly systems (FAS). Petri nets are used to model the systems. Through their liveness analysis, it characterizes two kinds of structural objects. Each object can lead to a siphon, and may cause the system to deadlock. Based on such objects, a necessary and sufficient condition about the liveness of Petri net models is obtained. In order to prevent each such object from causing FAS to deadlock, a Petri net controller is designed such that its induced siphon cannot be empty. The conjunction of all these controllers is proved to be capable of ensuring deadlock-free operation of a large class of FAS. The effectiveness of the proposed approach is shown via an FAS example.